A surface modification for hydrogen storage intermetallic particles by sol-gel method - Bocutti, R. [UNESP]; Saeki, M. J. [UNESP]; Ângelo, A. C. D. [UNESP] (My University, 2001)
A new process for the surface modification of hydrogen storage intermetallic particles used as anode material in secondary batteries is proposed in this article. The copper oxide particles coverage obtained by the sol-gel method is proposed to produce, under operational conditions of a Ni-MH battery, a metallic framework that tolerates the volume changes in charge/discharge cycles and does not inhibit the hydrogen absorption. Furthermore it was noticed an enhancement on the discharge capacity of the electrode material that can be related to a new hydrogen storage phase or to an inhibition of the surface oxidation promoted by the film coverage.
Keywords: Copper oxide; Hydryde; Ni-MH; Sol-gel; Surface modification